MicroRNA-137 promoter methylation is associated with poorer overall survival in patients with squamous cell carcinoma of the head and neck - Langevin, Scott M. (2010)
BACKGROUND: The overall 5-year survival rate of approximately 60% for head and neck cancer patients has remained essentially unchanged over the past 30 years. MicroRNA-137 (miR-137) plays an essential role in cell cycle control at the G1/S phase checkpoint. However, aberrant miR-137 promoter methylation observed in squamous cell carcinoma of the head and neck (SCCHN) suggests a tumor-specific molecular defect that may contribute to disease progression. METHODS: The goal of this study is to assess, in formalin-fixed paraffin-embedded tumor tissue, the association between miR-137 promoter methylation and survival (both overall and disease-free) and with prognostic factors including stage, tumor size, nodal positivity, tumor grade and surgical tumor margin positivity. RESULTS: Promoter methylation status of miR-137 was ascertained by methylation-specific PCR and detected in 11/67 SCCHN patients (16.4%), with no significant differences according to site (oral cavity, pharynx, larynx). Methylation of the miR-137 promoter was significantly associated with overall survival (Hazard Ratio = 3.68, 95% Confidence Interval: 1.01–13.38) but not with disease-free survival or any of the prognostic factors evaluated. CONCLUSIONS: This study indicates that miR-137 is methylated in tumor tissue from pharyngeal and laryngeal squamous cancers, in addition to oral squamous cell carcinoma; and that miR-137 promoter methylation has potential utility as a prognostic marker for SCCHN.